THE CONTRIBUTION OF EMPOWERMENT OF MADRASAH COMMITTEE AND TEACHER MOTIVATION TO THE IMPROVEMENT OF EDUCATION QUALITY OF MADRASAH IBTIDAIYAH SUB DISTRICT OF SUSUKAN, SEMARANG REGENCY - Fathan Budiman (Jurnal Ilmiah Pesantren, 2017)
This study includes a quantitative study with a study in MI Susukan District of Semarang District. The data analysis technique used is multiple regression analysis techniques. Research data sources, namely the management committee of the madrasah, madrassa teachers and accreditation results. The author takes a sample of the population using purposive sampling method. Methods of collecting data through questionnaires, interviews and documentation. The results showed that: 1) Empowerment madrasah committee in accordance with the data processing has an average score of 3.4 that is included in both categories; 2) Motivation of teachers in accordance with the data processing has an average score of 4.1 that is included in both categories; 3) There is an increase in the quality of education in the district of Susukan MI Semarang district by 4.6 points (4.6%) increased from 77.1 to 81.7 over the period 2005-2007 to 2009-2012; 4) There is a signifcant relationship between empowerment madrasah committee for improving the quality of education in the district Susukan MI Semarang Regency, the infuence of a variable rate of 0,100; 5) There is a signifcant relationship between motivation of teachers to improve the quality of education in the district of Susukan MI Semarang Regency, the infuence of a variable rate of 0,024; 6) There is a signifcant relationship between empowerment and motivation komita madrassa simultaneously to improve the quality of education in the district Susukan MI Semarang regency, with the degree of infuence of 0,008.